Pre-service mathematics teachers' responding to student thinking in their teaching experiences - Berna Tataroğlu Taşdan; Makbule Gözde Didiş Kabar (Journal of Pedagogical Research, 2022)
While noticing has received extensive attention from researchers with regards to pre-service and in-service teachers, there has been little research on how pre-service mathematics teachers respond to student thinking in the mathematical discussions. The aim of the study was to investigate pre-service mathematics teachers' (PSMTs) ways of responding to student thinking and the extent they focused on student thinking while responding to them. Two PSMTs' planned lessons were observed by the university supervisor and the cooperating teacher. Data was collected through lesson plans, video recordings of the PSMTs' teaching and the observation notes by the supervisor. The constant comparative method was performed throughout the qualitative data analysis. The results initially revealed that although PSMTs could use different types of actions such as eliciting, repeating, redirecting, teaching and encouraging to respond to student thinking during their teaching experiences, their responding to student ideas did not follow a single path or a pattern for their lessons. In terms of the ways of responding, PSMTs dominantly used eliciting, repeating, and evaluating, while explaining, extending and probing student thinking were less preferred. The results provide important cases to help mathematics teacher educators to understand the PSMTs' ways of responding to student thinking and their tendencies towards being able to focus on student thinking while responding to them. Finally, the paper discusses the educational implications of the results.